Nilai-Nilai Pendidikan Multikultural dalam Al-Qur’an Surat Al-Hujurat Ayat 13 - Muhammad Fadillah Mochtar; A. Mujahid Rasyid (UNISBA Press, 2022)
Abstract. The background of this research is the multicultural situation in Indonesia. Indonesia's wealth is a source of strength as well as a potential source of problems. Many conflicts arise because of fanaticism and lack of tolerance. Multicultural education is considered very relevant to the Qur'an which contains universal values. The formulation of the problem raised in this study is about the values of multicultural education in the Qur'an Surah Al-Hujurat verse 13 and the relevance of multicultural education to Islamic education. This study aims to determine the values of multicultural education contained in the letter Al-Hujurat verse 13 and the relevance of multicultural education with Islamic education. This research is a type of library research, namely research in which the object of research is explored through various library sources. To discuss the problems in this research, the preparation uses a maudu'i interpretation study approach. This method the author uses to analyze verses that talk about the same theme, which then relates the preparation to an explanation of multicultural education. So that a common ground can be found, that the Qur'an has also explained the multicultural values contained in it. The results of this study indicate that multicultural education in Q.S Al-Hujurat verse 13 contains 1) the values of multicultural education: a) peace, b) justice, c) brotherhood, d) respect and respect, e) tolerance. 2) multicultural education is very relevant to the goals of Islamic education that students are expected to become human beings with noble character and can appreciate the diversity of cultures around them. Multicultural education is very important to be taught as an educational science that is needed by all people. Abstrak. Penelitian ini berlatar belakang karena keadaan Indonesia yang multikultur. Kekayaan yang dimiliki Indonesia merupakan sumber kekuatan sekaligus sumber potensi timbulnya persoalan. Banyak konflik yang timbul karena fanatisme dan kurang nya sikap toleransi. Pendidikan multikultural dirasa sangat relevan dengan A-Qur’an yang mengandung nilai-nilai universal. Rumusan masalah yang diangkat dalam penelitian ini yaitu mengenai nilai-nilai pendidikan multikultural dalam AlQur’an surat Al-Hujurat ayat 13 dan relevansi pendidikan multikultural dengan pendidikan islam. Penelitian ini bertujuan untuk mengetahui nilai-nilai pendidikan multiultural yang terkandung dalam surat Al-Hujurat ayat 13 dan relevansi pendidikan multikultural dengan pendidikan islam. Penelitian ini adalah penelitian jenis library research, yaitu penelitian di mana objek penelitiannya digali lewat berbagai sumber kepustakaan. Untuk membahas permasalahan-permasalahan dalam penelitian ini, penyusunan menggunakan pendekatan kajian tafsir maudu’i.metode ini penulis gunakan untuk menganalisis ayat-ayat yang membicarakan tema yang sama, yang kemudian penyusunan kaitkan dengan paparan mengenai pendidikan multikultural. Sehingga dapat ditemukan titik temu, bahwa Al-Qur’an pun telah menjelaskan nilai-nilai multikultural yang terkandung di dalamnya. Hasil penelitian ini menunjukkan pendidikan multikultural dalam Q.S Al-Hujurat ayat 13 mengandung 1) nilai-nilai pendidikan multikultural : a) perdamaian, b) keadilan, c) persaudaraan, d) menghargai dan menghormati, e) toleransi. 2) pendidikan multikultural sangat relevan dengan tujuan pendidikan islam bahwa siswa diharapkan dapat menjadi manusia yang berakhlak mulia dan dapat menghargai keberagaman budaya di sekitarnya. Pendidikan multikultural sangat penting untuk di ajarkan sebagai ilmu pendidikan yang sangat di butuhkan oleh semua kalangan.